2019
DOI: 10.1371/journal.pgen.1008497
|View full text |Cite
|
Sign up to set email alerts
|

East-Asian Helicobacter pylori strains synthesize heptan-deficient lipopolysaccharide

Abstract: The lipopolysaccharide O-antigen structure expressed by the European Helicobacter pylori model strain G27 encompasses a trisaccharide, an intervening glucan-heptan and distal Lewis antigens that promote immune escape. However, several gaps still remain in the corresponding biosynthetic pathway. Here, systematic mutagenesis of glycosyltransferase genes in G27 combined with lipopolysaccharide structural analysis, uncovered HP0102 as the trisaccharide fucosyltransferase, HP1283 as the heptan transferase, and HP15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 48 publications
(84 reference statements)
6
23
0
Order By: Relevance
“…S2 †) by an asyet uncharacterized mechanism, yet has no effect on lipopolysaccharide biosynthesis. 66 Small molecule-induced functional defects appeared even more striking than those induced via genetic interruption. Fitness appeared to be most impaired in H. pylori treated with BnBac (1), F-DAT (5) and BnFucNAc (3) (Fig.…”
Section: Metabolic Inhibitors Elicit Functional Defects In H Pylorimentioning
confidence: 99%
“…S2 †) by an asyet uncharacterized mechanism, yet has no effect on lipopolysaccharide biosynthesis. 66 Small molecule-induced functional defects appeared even more striking than those induced via genetic interruption. Fitness appeared to be most impaired in H. pylori treated with BnBac (1), F-DAT (5) and BnFucNAc (3) (Fig.…”
Section: Metabolic Inhibitors Elicit Functional Defects In H Pylorimentioning
confidence: 99%
“…The HP0102 protein sequence contains several motifs of the glycosyltransferase family 2 (GT-2; www.kegg.jp , http://pfam.sanger.ac.uk/ , http://www.cazy.org/ ), suggesting HP0102 is involved in LPS biosynthesis. While at the time of this study, the precise function of HP0102 was unknown, it was recently described to act as a fucosyltransferase involved in O-chain biosynthesis in H. pylori strain G27 10 . In line with the study by Li and colleagues 10 , we also observed that H. pylori X47-2AL ∆ hp0102 deletion mutants have only rough-form LPS, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This long O-antigen comprises a trisaccharide (Trio), a glucan, a DD-heptan, and terminal Lewis antigens. Despite its important roles in immune evasion and persistence, a complete picture of the LPS biosynthesis pathway in H. pylori is only being revealed stepwise 4 , 9 , 10 . This might be due to the dispersed genomic locations of LPS genes throughout the H. pylori genome.…”
Section: Introductionmentioning
confidence: 99%
“…This operon encodes the TlpB chemotaxis receptor and the HP0102 protein that was shown to function as a glycosyltransferase involved in lipopolysaccharide (LPS) O-chain biosynthesis (Pernitzsch et al, 2021). The precise fucosyltransferase activity of HP0102 was shown (Li et al, 2019). The sRNA designated RepG (REgulator of Polymeric G-repeats) is highly conserved in H. pylori.…”
Section: Trans-acting Regulatory Srnas Of H Pylorimentioning
confidence: 99%